Evaluation of the Company Size Effect on Latin American Stock Markets (2013)
This paper assesses the existence of the size effect on the most important stock markets in Latin America (Argentina, Brazil, Chile, Colombia, Mexico and Peru) for the period between 2002 and 2012, using the cross-section contrast methodology of the size effect in the CAPM context -- Results show that there is reversed effect in some of the Latin American markets